Factors Affecting Environmental Management by Small and Micro Firms: The Importance of Entrepreneurs' Attitudes and Environmental Investment. (17th September 2015) - Testa, Francesco; Gusmerottia, Natalia Marzia; Corsini, Filippo; Passetti, Emilio; Iraldo, Fabio
Abstract: The paper investigates (1) the influence of external pressures, internal factors, and environmental attitudes of entrepreneurs on environmental proactive strategy in small and micro firms and (2) whether environmental proactive strategy impacts environmental investment and environmental performance. The study is based on a survey conducted in Italy and tests the set of hypotheses using a structural equations model. The results underline that external pressures and entrepreneurs' attitudes are the most important predictors of environmental proactivity both for small and micro firms. The results also confirm a positive relationship between environmental proactivity and environmental investments as well as environmental performance. Yet, environmental investments show a strong influence on environmental performance. Commitment to environmental management by small and micro firms appears thus on the ground, showing that some substantive actions have started to be developed. Copyright © 2015 John Wiley & Sons, Ltd and ERP Environment